An examination of the factors underlying decision-making about selection and presentation of photographs of political conflict in South African newspapers - O'Dowd, Catherine Frances (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1997)
What newspaper readers see of an event is detennined by what photographs are seley ted and how they are presented. This thesis attempts to deconstruct the decision-making process around selection and presentation of photographs, with the aim of detennining what factors are taken into account in that process. It is based on the hypothesis that there must be a number of factors involved in decisions about news photographs, although these factors may not necessarily be consciously acknowledged in the decision-making process. The study involves a comparison of how five case studies of incidents of political violence, which occurred between 1990 and 1994 in South Africa, were used'in lrinewspapers. The focus on images of political violence is based on the assumption that politically and visually controversial images will give rise to situations in which gatekeepers will be caned upon to question their decisions. The research is based on qualitative research interviews with the decision-makers involved in the case studies. The analysis of the decision-making procedures is based on the theory of gatekeeping. The interviews are analysed in terms of Lewin's theory offqrces, which suggests that, depending on the context, some factors will manifest themselves as positive forces working in favour of the photograph being selected or well presented, while others will take the form of negative forces. The analysis sets out to determine what factors were taken into account in the decision::making process, what detennined their relative degrees of importance and how those relative degrees of importance determined the final outcome. Following an introduction to the practical case study research, dealing with general issues such as picture policy in newspapers and decision-making procedures, each case study is dealt with in turn. After an outline of the context in which the event occurred, the kinds of pictures that were available to the newspapers are described. Then the decisions taken about which to choose and how to use them are analysed in terms of dominant themes. These are themes such as newsworthiness, gruesomeness of content and concern abo!Jt what other media were using. The analysis examines the way the news context and the decision-making context determine the relative importance of the various factors present. Finally the study looks at the conclusions that can be drawn from the five case studies. The conclusion supports the initial hypothesis in finding that these decisions can be shown to have their basis in a fairly limited set of factors. The different results, from study to study and from newspaper to newspaper within a study, are determined by the changing news context and the decisi~n-making context.
Keywords: Photojournalism; Photojournalism -- South Africa; Photojournalists -- South Africa; South Africa -- Politics and government -- 1989-1994